Effective email : concise, clear writing to advance your business needs - Terk, Natasha (Gildan, 2018)
In today's fast-paced, competitive business environment, we all need to communicate clearly and use our time productively. Even seasoned writers will find tips, tools, and ideas in this book that can improve the quality--and reduce the quantity--of email in the workplace. This book will help you write concise, clear emails that advance your business needs.